An SOC Approach to Study the Solar Wind‐Magnetosphere Energy Coupling. Issue 4 (8th April 2019) - Banerjee, Adrija; Bej, Amaresh; Chatterjee, T. N.; Majumdar, Abhijit
Abstract: Solar wind‐magnetosphere interaction and the injection of large quantity of plasma particles into the Earth's magnetosphere are the primary reasons behind geomagnetic storm, auroral effects, and, in general, all the fluctuations observed in the terrestrial magnetic field. In this paper, we analyzed the perturbed magnetosphere as a sandpile‐like cellular automata model based on the concept of self‐organized criticality and many‐body interactive system and proposed a solar wind‐magnetosphere energy coupling function in terms of interplanetary magnetic field B Z, the z th component of interplanetary magnetic field. The function determines the cusp width W depending on the intensity of (− B Z − B Th ) where B Th is the threshold value. The model generates two output series, which are the numerical representation of the real‐time Dst index and AE index series, respectively. For our study, the range of years 1997–2007 of the 23rd solar cycle had been considered here. The threshold value B Th plays a significant role in the analysis and exhibits a proportional relationship with the yearly mean total number of sunspots for each year of the range 1997–2007 of the 23rd solar cycle. For each year, the two resultant output time series of the model display high‐correlation coefficients with the real‐time Dst and AE indexes, respectively, which denotes the acceptability of the proposed energy coupling function and its relation with the solar activities. Key Points: The solar wind‐magnetosphere coupling has been analyzed using a cellular automata model based on the concept of self‐organized criticality A new coupling function is introduced to determine the cusp width A threshold value of B Z, the z th component of the interplanetary magnetic field related to the yearly mean total number of sunspots, is introduced